KONFLIK KERJA-KELUARGA DAN WORK ENGAGEMENT KARYAWATI BALI PADA BANK DI BALI - Kesumaningsari, Ni Putu Adelia; Simarmata, Nicholas (Program Studi Sarjana Psikologi, Fakultas Kedokteran, Universitas Udayana, 2014)
The complexity life roles of Balinese Woman have been a challenge for them who work in formal sector. Balinese Woman is bounded by customs duties as part of the fulfillment of their domestic role in the family. Undergoing role in a balanced work and family often lead to work-family conflict, then giving impact to reduce work engagement among them. Work engagement characterized by vigor, dedication, and absorption during work (Schaufeli, Salanova, Gonzalez-Roma, & Bakker, 2002). Work engagement is really required by the industrial sector workers who need to involves quality of service as the main capital (Indrianti & Hadi, 2012), such as banking sector. Hence, this study aimed to examine the relationship between work-family conflict and work engagement on Balinese Woman employees at banking sector in Bali. This research uses quantitative method. Respondents involved are 121 Balinese Woman employees who have had family, educated at least bachelor degree (S1), and at least have been working for 1 year in their company. Research validity uses content validity and items test empirically through internal consistency procedure. Reliability score for work-family conflict scale shows 0.944 and reliability score for work engagement shows 0.910. Data distribution has shown normal and linear distribution. Results of simple regression analysis shows negative and significant relationship between work-family conflicts with work engagement on Balinese Woman Employee at banking sector in Bali (B= -0.411; p= 0,002). Contribution of work-family conflict variable on work engagement is 8.1% and the remaining 91.9% is influenced by other factors. Keywords: Work-family Conflict, Work Engagement, Balinese Woman Employees at Banking Sector in Bali